Factors Associated with Productive Recruiting in a Respondent-Driven Sample of Men who Have Sex with Men in Vancouver, Canada. - Forrest, Jamie; Lachowsky, Nathan; Lal, Allan; Cui, Zishan; Sereda, Paul; Raymond, Henry; Ogilvie, Gina; Roth, Eric; Moore, David; Hogg, Robert; Forrest, Jamie I; Lachowsky, Nathan J; et al. (Journal of Urban Health, 2016)
Respondent-driven sampling (RDS) has become a preferred sampling strategy for HIV research and surveillance in many global settings. Methodological investigation into the validity of RDS-generated samples has helped improve theoretical components of design. However, the operational challenges of implementing RDS remain underreported. We sought to identify factors independently associated with productive recruiting in an urban RDS-generated sample of gay, bisexual, and other men who have sex with men (MSM). Data were collected from the Momentum Health Study, a cohort of MSM recruited by RDS in Vancouver, Canada. Eligible men were given up to six RDS coupons to recruit their peers. The primary outcome was a count variable of each participant's number of eligible recruits. Multivariable Poisson regression identified independent predictors of productive recruitment. In total, 719 individuals comprised this analysis, of which 119 were seeds. The distribution of eligible recruits was right skewed, with 391 (54.4 %) having never recruited another participant and only eight participants (1.1 %) having recruited five. Significant, independent predictors of recruiting one additional participant included network size per ten unit increase (adjusted risk ratio [aRR] 1.03), being of Aboriginal race/ethnicity compared with White (aRR 1.51), being HIV-positive (aRR 1.31), being sexually active with only males (aRR 2.48), being single compared with common law/married (aRR 1.37), having recently read gay newspapers (aRR 1.58), having recently sought sex partners online (aRR 1.33) and being out to a male parent (aRR 1.30). This analysis demonstrates the importance of social network size in RDS adjustment, but also identifies other socio-demographic and behavioral variables that increased RDS coupon return, which may help researchers better operationalize the implementation of RDS.